View of the pillars of the Mukhamandapa of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
This is the closer view of the pillars of the mukhamandapa (front porch) of the Mahanaleshwar Temple. The four pillars, two on either side of the entrance, support the rectangular ceiling. The pillars of the mukhamandapa are square and of the ghatpallava variety, meaning one block is decorated with vases and foliage motifs.